2021
DOI: 10.3389/fenvs.2021.609621
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Swine Manure Impact on Soil Nutrients and Carbon Under Controlled Leaching Experiment Using a Midwestern Mollisols

Abstract: Biochar application to the soil can improve soil quality and nutrient leaching loss from swine manure adapted soils. Our working hypothesis was that the biochar-incubated with manure could be a better soil amendment than conventional manure application. The manure-biochar application to the soil would decrease nutrient leaching from manure and increase plant-available nutrients. The study objectives were to 1) assess the physicochemical properties of the manure-biochar mixture after lab incubation and 2) evalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 39 publications
1
43
1
Order By: Relevance
“…Results comparing the changes in manure properties confirmed that acidic biochar could mitigate NH3 emissions and likely prevent nitrogen loss in the manure. Manure treated with biochar powder showed benefits to soil health, lowered nutrient runoff risk, and the potential for agronomic benefits to corn and soybeans (Banik et al, 2021a(Banik et al, , 2021b shown on lab and greenhouse scales. In addition, more techno-economic analyses are warranted on the potential savings due to the nutrient retention in manure, as the average cost of anhydrous ammonia is $526/ton (USDA, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results comparing the changes in manure properties confirmed that acidic biochar could mitigate NH3 emissions and likely prevent nitrogen loss in the manure. Manure treated with biochar powder showed benefits to soil health, lowered nutrient runoff risk, and the potential for agronomic benefits to corn and soybeans (Banik et al, 2021a(Banik et al, , 2021b shown on lab and greenhouse scales. In addition, more techno-economic analyses are warranted on the potential savings due to the nutrient retention in manure, as the average cost of anhydrous ammonia is $526/ton (USDA, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Biobased-fuels production, waste-to-carbon, and waste-to-energy thermal processes result in a relatively low-value biocoal. Circular economy opportunities exist for the valorization of biochar and the improvement of sustainability in animal and crop production systems (Banik et al, 2021a;Banik et al, 2021b). The long-term goal is to test and scale up the treatments from laboratory-scale to farm-scale, keeping in mind the techno-economic constraints for many swine farmers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biobased-fuel production, waste-to-carbon, and wasteto-energy thermal processes result in a relatively low-value biocoal. Circular economy opportunities exist for the valorization of biochar and the improvement of sustainability in animal and crop production systems [22,23]. The long-term goal is to test and scale up the treatments from the laboratory scale to the farm scale, keeping in mind the techno-economic constraints for many swine farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, synergistic effects to biochar use could be achieved for the animal-crop production system. First, biochar can be used to mitigate gaseous emissions from manure, and then the biochar and manure mixture can be used as a better-quality fertilizer, improve the soil nutrients content, and minimize the nutrient losses from soil [22,23]. Therefore, innovative biochar treatment could be a one-stop solution to solve the gaseous emissions and improve agriculture's sustainability.…”
Section: Introductionmentioning
confidence: 99%